Epidemiology of breast cancer in Patos de Minas (Research, Society and Development, 2024)
Breast cancer is a malignant neoplasm resulting from the disordered growth of breast tissue cells and is the most common type of cancer among women in Brazil, except for non-melanoma skin cancers. Its incidence is particularly high in the South and Southeast regions, with an estimated 73,610 new cases annually between 2023 and 2025, according to data from the National Cancer Institute (INCA). The objective of this article is to present an epidemiological study of breast cancer. This study is characterized as a quantitative and descriptive epidemiological survey on breast cancer in Patos de Minas, Minas Gerais, based on data collected from the Cancer Information System (SISCAN) and the Breast Cancer Information System (SISMAMA) between July 2020 and July 2024. Data on the number of mammograms performed in five consecutive years were analyzed, which revealed a decrease in the number of exams performed in 2021 and 2022, possibly influenced by the COVID-19 pandemic, which limited access to health services. Thus, the year with the most significant results was 2023, after the pandemic period. In addition, the BI-RADS system was used to categorize the findings, with most exams classified as benign (category 2). A higher prevalence of cases was also observed in women between 45 and 49 years old, and differences in the distribution of findings by race/color, with disparities in access to screening services between white and black women.